Pharmacological Properties of Ginsenoside Re - Gao, Xiao-Yan; Liu, Guan-Cheng; Zhang, Jian-Xiu; Wang, Ling-He; Xu, Chang; Yan, Zi-An; Wang, Ao; Su, Yi-Fei; Lee, Jung-Joon; Piao, Guang-Chun; Yuan, Hai-Dan (Frontiers in Pharmacology, 2022)
Ginsenoside Re is a protopanaxatriol-type saponin extracted from the berry, leaf, stem, flower bud, and root of Panax ginseng. In recent years, ginsenoside Re (Re) has been attracting attention as a dietary phytochemical. In this review, studies on Re were compiled by searching a combination of keywords, namely “pharmacology,” “pharmacokinetics,” and “toxicology,” in the Google Scholar, NCBI, PubMed, and Web of Science databases. The aim of this review was to provide an exhaustive overview of the pharmacological activities, pharmacokinetics, and toxicity of Re, focusing on clinical evidence that has shown effectiveness in specific diseases, such as diabetes mellitus, nervous system diseases, inflammation, cardiovascular disease, and cancer. Re is also known to eliminate virus, enhance the immune response, improve osteoporosis, improve skin barrier function, enhance intracellular anti-oxidant actions, regulate cholesterol metabolism, alleviate allergic responses, increase sperm motility, reduce erectile dysfunction, promote cyclic growth of hair follicles, and reduce gastrointestinal motility dysfunction. Furthermore, this review provides data on pharmacokinetic parameters and toxicological factors to examine the safety profile of Re. Such data will provide a theoretical basis and reference for Re-related studies and future applications.